POTENSI SPIRULINA (ARTHOSPIRA PLATENSIS) DALAM PEMBUATAN CLAY MASK UNTUK PERAWATAN KULIT ALAMI - Jumrodah, Jumrodah; Astuti, Nila; Anisa, Nor; Fitriani, Tilka; Alia, Rahmah ((JITEK)Jurnal Ilmiah Teknosains, 2025)
Natural clay mask is a safe and effective alternative for skin care. This study aims to develop a clay mask based on Spirulina, enriched with sali-cylic acid, Centella asiatica, and clay, for natural skin care innovation. Three formulations were tested with different composition variations: (1) salicylic acid 0.50 g, Centella asiatica 5 mL, clay 10 mL; (2) salicylic acid 0.20 g, Centella asiatica 2.5 mL, clay 20 mL; and (3) salicylic acid 0.20 g, Centella asiatica 2.5 mL, clay 10 mL. The results showed that all formulations were physically stable with a pH suitable for the skin. Hedonic tests were conducted on 20 student respondents to evaluate preferences for the formulations. Respondents gave assessments based on as-pects of texture, aroma, color, and comfort of use. Formulation C1 is effective for acne-prone skin, C2 excels in spreadability for oily skin, and C3 provides a balance between cleansing and moisturizing. The combination of nutrient-rich Spirulina sp., clay, salicylic acid, and Centella asiatica produces a product that not only cleanses deeply, but also provides nutrition and prevents hydration to the skin. This product is safe, environmen-tally friendly, and has great potential to be developed in the cosmetic industry as a natural skin care.